OPTIMASI MEDIA DAN TEKNIK STERILISASI UNTUK MENINGKATKAN KUALITAS MISELIUM BIBIT F2 JAMUR TIRAM (Pleurotus ostreotus) - M, Hatta,; A.A.R, Agussalim, (Percetakan Umi Toaha Makassar, 2024)
F2 seeds are a derivative of F1 cultivation grown in a medium containing cellulose. Sorghum seeds and corn seeds contain cellulose, hemicellulose, and lignin that can be used as innovative media for F2 seedling development and the growth of oyster mushroom mycelium. The purpose of this research is to determine the growth of F2 oyster mushroom mycelium on media of sorghum seeds and corn seeds that have been sterilized for 40 minutes and 60 minutes. The type of research used is an experiment with a Completely Randomized Design (CRD) in a factorial pattern consisting of 2 factors. Factor 1 is the media type: Sorghum Seeds, and corn Seeds. Factor 2 is the Sterilization Time: 60 minutes and 40 minutes. The parameters measured are the length of the mycelium, the spread of the mycelium, and the thickness of the mycelium in F2 oyster mushroom seedlings. Technical analysis uses quantitative descriptive data. Based on the results obtained regarding the growth of the F2 oyster mushroom mycelium, the highest growth was observed on sorghum seed media, measuring 13.81 cm, with a very thick and dense spread. The cellulose content affects the growth of the mycelium. Meanwhile, the lowest growth of the F2 oyster mushroom mycelium was found on corn seed media, measuring 11.27 cm, with a thin and uneven spread, and a density or thickness that is thin and sparse.